SN-CUO-ARABIC GUM COMPOSITION FOR RED TRACER PROJECTILE AMMUNITION POTENTIAL - Abdul Basyir; Nining Sumawati Asri; Didik Aryanto; Isnaeni Isnaeni; Cherly Firdharini; Wahyu Bambang Widayatno; Agus Sukarto Wismogroho; Diang Sagita; Denny Lesmana (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
Fundamentally, tracer projectile material based on pyrotechnic composition, and where the pyrotechnic was generally composed of fuel, oxidizer, and binder. The tin (Sn) material is one of the candidates for fuel material because tin has a low melting point, so this composition can ignite at low temperature, while the copper oxide (CuO) can emit the orange-red spectrum. This study aims to evaluate the thermal and spectrum character of Sn-CuO-AG-based composition. The characterization data of these samples was evaluated by tests of morphology and phase, enthalpy change, calorie energy, and spectrum emission. Based on this data, the 17Sn-68CuO-15AG sample was emitted a strong red color too, but this sample has a high or the longest exothermic process. Furthermore, the 27Sn-58CuO-15AG sample has emitted a weak red color with medium exothermic energy. Generally, the 22Sn-63CuO-15AG is more suitable than the two other compositions for the tracer projectile composition of ammunition, this material emits a strong red spectrum and low-calorie energy.